Penerapan Rest API Pada QR Code Untuk Validasi Surat Administrasi Desa - Binanda Wicaksana; Gendi Telamdika (Universitas Binaniaga Indonesia, 2023)
As one of the lower-level government agencies, the village has an important role in a government. One of the important roles of the village is serving the community in making administrative letters, for example in making death certificates, business, domiciles and others. Currently the process of making administrative letters is not optimal which causes the process of making administrative letters takes quite a long time and the problem is often queues and there is no certainty that the administrative letter will be completed on that day besides that the community cannot fill out the village head's signature on the letter due to the busyness of the village head which requires him to be often out of the office or have many activities so a system is needed that can make it easier for village officials to get legitimacy letters and serving the community in making administrative letters, this study uses the Rest API on the QR Code for validation in administrative letters in the village, where Rest api uses the http protocol where the API link will be entered with a QR Code and this Rest API as link the QR Code to the web. By implementing the Rest API on the QR code for validating administrative letters in the village, a feasibility test has been carried out and obtaining a value of 82.5%, which means that the application is very feasible, and can help process administrative letters in the village.